2009
DOI: 10.1116/1.3116586
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of perpendicular CoPt magnetic nanodot arrays patterned by nanosphere lithography

Abstract: Perpendicular anisotropy Co80Pt20 films were patterned into nanopillars of 40–90nm using nanosphere lithography. A monolayer of polystyrene spheres was coated onto the sputtered films and size tailored by reactive ion etching in oxygen. These reduced spheres were used as masks for ion milling of the magnetic films. Increased coercivity and squareness resulted in decreasing nanopillar size. A significant increase in intrinsic coercivity was demonstrated with the decrease in pillar size. The reversal mechanism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The diameter was found to be about 30 nm, larger than that of the PFS nanospheres, which may result from the self-shadowing effect during the ion-milling process. 26 It was also observed that etching for a long time (5 min) at near normal incidence (85 ) smoothed the surface as shown in Figure 2(c). This may be caused by the disappearance of the PFS mask under these etching conditions.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…The diameter was found to be about 30 nm, larger than that of the PFS nanospheres, which may result from the self-shadowing effect during the ion-milling process. 26 It was also observed that etching for a long time (5 min) at near normal incidence (85 ) smoothed the surface as shown in Figure 2(c). This may be caused by the disappearance of the PFS mask under these etching conditions.…”
Section: Methodsmentioning
confidence: 74%
“…This may be caused by the disappearance of the PFS mask under these etching conditions. 26 In-plane M-H loops of the continuous film and those patterned by ion-milling at 55 to 85 for 2 to 5 min are presented in Figure 3 for comparison. It can be seen that M-H loops depend on ion-milling angle and time; except for the sample milled at 85 for 5 min, all other milled samples show enhancement of coercivity.…”
Section: Methodsmentioning
confidence: 99%
“…Low cost top-down methods include nanosphere and nanoparticle lithography. In these methods, masks can be produced by assembling nanospheres or nanoparticles into close-packed arrays onto wafers by spin coating or the Langmuir-Blodgett method [2,3]. The spacing and diameter can be controlled by the size of the nanoparticles or nanospheres.…”
Section: Introductionmentioning
confidence: 99%
“…The spacing and diameter can be controlled by the size of the nanoparticles or nanospheres. Other lower cost techniques include diblock copolymer lithography, [2] anodized aluminum oxide (AAO) lithography, [4,5] colloid lithography, laser interference lithography etc. for specific fabrication application purposes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For that purpose colloidal particles (natural lithography [55]) or polystyrene nanospheres are frequently used (nanosphere lithography [56]). On the one hand the self-assembled polystyrene spheres are covered by magnetic films and multilayers which creates separated nanodots on the top of the spheres [57] while on the other hand reactive ion etching or ion milling is used to clone the periodic structure into a magnetic thin film system [58,59]. To tune the diameter as well as the spacing of the particles the organic spheres are shrunk in a plasma etching step before structure transfer [60][61][62].…”
Section: Introductionmentioning
confidence: 99%